Corporate Finance : going public and issuing new equity and takeovers, mergers and disposals - Sabine, Martin . (London : Butterworths, 1987)
Describes the theory, principles and practice of corporate finance, that is to say the major activities carried on by the corporate finance department of an organization.
Includes index
lje 2/7/2017
Loans
Keywords: Corporations Finance; Industrial management